Religious Tolerance and Division in the Krajina: The Croatian Serbs of the Habsburg Military Border - Roksandić, Drago (1997)
The author evaluates religious factors in the Habsburg Military Border in Early Modern Period from a cultural and ethnic viewpoint, analysing along the way competing imperial and Church ambitions in the area.
Projekt MZOS
ENG